An SFL Analysis of English Grammatical Features in BBC and Reuters News Reports on the Indonesia–US Trade Agreement - Dini Vidya Salsabila; Citra Nur Aziza; Chalimah Chalimah (Universitas Negeri Surabaya, 2026)
News reports play an important role in communicating political and economic events to global audiences. Beyond conveying information, news texts construct meanings through various linguistic resources that shape readers’ understanding of events. This study investigates English grammatical features in two international news reports discussing the Indonesia–US Trade Agreement published by BBC and Reuters on 20 February 2026. The study employs the framework of Systemic Functional Linguistics (SFL), particularly the ideational metafunction and transitivity system, to examine how grammatical features contribute to meaning construction in economic news discourse. The data consist of two news reports covering the same economic event, allowing a comparative analysis of linguistic choices across different media institutions. Using a qualitative content analysis approach, the study focuses on four grammatical features: parts of speech that express connecting relationships, expletive it and there, derivational forms of verbs, and descriptive adjectives. The findings indicate that connecting relationships are the most frequently occurring feature in both reports, followed by derivational verbs and descriptive adjectives, while expletive constructions occur only minimally. Furthermore, the identified grammatical features are predominantly associated with material and relational processes within the transitivity system. These findings demonstrate that grammatical choices contribute significantly to the representation of economic actions, evaluations, and institutional relationships in news discourse. The study is expected to contribute to the application of SFL in media discourse analysis and provide authentic examples for grammar and discourse analysis courses in English language education.